The Impact of Transformational Leadership on Knowledge Acquisition and Transfer: The Mediating Roles of Employee Engagement and Autonomy - Tuyen, Nguyen Thi (International Journal of Scientific Research and Management (IJSRM), 2025)
In the context of digital transformation, the role of transformational leadership in the acquisition and transfer of knowledge within organizations is becoming increasingly significant. Therefore, this study aims to measure and empirically test a conceptual model that clarifies the impact of transformational leadership on knowledge acquisition and transfer, through the mediating roles of employee engagement and autonomy in Hanoi. Furthermore, the study examines the mediating relationship of employee engagement and autonomy in the relationship between transformational leadership and knowledge acquisition and transfer. The research findings indicate that all four factors—transformational leadership, employee engagement, autonomy, and knowledge acquisition and transfer—interact with each other. The research data was analyzed using Structural Equation Modeling (SEM) to test the scales and research model. The results show that the research objectives were fully achieved. The empirical evidence demonstrates the positive relationship between transformational leadership and employee engagement, as well as the positive effects of employee engagement on autonomy and knowledge acquisition and transfer among employees. Consequently, this study contributes valuable insights to both theory and practice, and suggests new research directions for the future.